ANALISIS KINERJA KEUANGAN BANK SYARI’AH MENGGUNAKAN METODE ECONOMIC VALUE ADDED (STUDI KASUS BANK MUAMALAT INDONESIA TBK.) - NURUL FAUZIAH, YUSTIN Nurul (Jurnal Akuntansi AKUNESA, 2012)
The aim of this research is to analyse the financial performance of Bank Muamalat Indonesia Tbk with using Economic Value Added (EVA). This research using qualitative method. The research result using data financial report period 2008-2010 show that the best performance in 2008. In 2009 value of EVA less than zero, it means that the financial performance Bank Muamalat Indonesia Tbk. are fail contribute to economic value added for the firm, especially for shareholder wealth and investors. Exactly in 2010 value of EVA increase until 71% in comparison with 2009. Kata Kunci: EVA, Analisis Kinerja, Bank Syariah,